The 1966 International Covenant on Economic, Social and Cultural Rights (ICESCR) - Kogej, Katarina; Strban, Grega (The Universal Protection of Human Rights, 2026)
Abstract: The International Covenant on Economic, Social, and Cultural Rights (ICESCR), adopted in 1966, is a part of the International Bill of Rights, alongside the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights. It codifies key economic, social, and cultural rights (ESCR), such as the right to work, health, education, and an adequate standard of living, while emphasising their progressive realisation. Despite its significance, the ICESCR faces challenges in enforcement, with the absence of strong, binding mechanisms. Chapter 1 outlines the significance of the International Bill of Rights, while Chapter 2 explores René Cassin’s vision of integrating all human rights, including ESCR, into the UDHR and compares it to the ultimate separation in the Covenant, examining the challenges surrounding ESCR, such as debates on justiciability. Chapter 3 discusses the adoption, relevance and implementation of the ICESCR, showing its widespread ratification and exploring different aspects and measures of implementation, including the process and circumstances regarding the adoption of the Optional Protocol in 2008. Chapter 4 compares the ICESCR with the European Social Charter, the European Convention on Human Rights and the EU Charter of Fundamental Rights. Chapter 5 breaks down the structure of the ICESCR, detailing rights-based obligations imposed by part I and III and the general obligations stemming from part II of the Covenant. Procedural obligations regulated by part IV are discussed in Chapter 6, where the role of the Committee on Economic, Social, and Cultural Rights (CESCR) in monitoring the ICESCR is analysed. Although its decisions are non-binding, studies of cases from the Individual communications’ procedure illustrate its impact on housing, social security, and health rights. As no cases involving Central or Eastern European countries have been published under the Individual communications’ procedure, Chapter 7 highlights selected recommendations from the Concluding Observations on the periodic reports of Montenegro, Slovenia, and Czechia. Despite its limitations, the ICESCR remains a cornerstone of global human rights advocacy, influencing both national legislation and international norms. Keywords: ICESCR, economic, social and cultural rights, progressive realisation, CESCR, monitoring